Crossover from Reverse Saturable to Saturable Absorptions in Two-Dimensional Tungsten Disulfide - Neupane, T.; Adhikari, C. M. (Journal of Nepal Physical Society, 2022)
The Tungsten disulfide atomic layer has enormous scientific merits that play a key role in the nonlinear absorption process. Four distinct excitonic peaks in the absorption spectra are crucial for identifying the polarity of nonlinear absorption by virtue of the resonant or non-resonant excitation process. The excitation source of 532 nm is enough for the one-photon optical transition at both low-energy excitonic peaks and two-photon transition at both higher-energy excitonic peaks. The Tungsten disulfide atomic layer exhibited the reverse saturable (or positive nonlinear) absorption through the two-step excitation process which could be possible due to the optical transition at the higher energy excitonic peaks. In addition, the polarity of the nonlinear absorption coefficient and its interchange have been analytically studied with the aid of a magnitude of excited-state absorption cross-section and Ground-state absorption cross-section. Besides, the various possible factors affecting the Z-scan results are discussed.